AESI promoted active dialogue among students on several topics of international relations in this pandemic period - Massimo Maria Caneva (Freedom from Fear, 2020)
Preparing young people for the diplomatic and international careers of today means facing the new international crises with an innovative and global vision that analyzes their real causes first and then provides adequate and effective responses over time. Furthermore, a greater synergy with international organizations such as the United Nations (UN) is needed. In this regard, the European Association of International Studies (AESI) usually organizes two missions in Geneva in coordination with the Italian Representation at the United Nations agencies. Unfortunately, the health emergency has not allowed this tradition to continue this year, but the liaison with the Director-General of the UN Agencies in Geneva, Ms. Tatiana Valovaya, is still vigorous and the activities promoted by AESI for young university students are considered of great importance. Indeed, AESI is strongly convinced that only by investing in the new generations with innovative and global training, which envisage above all concrete contacts with international actors such as the UN and the European Union (EU), we can achieve a future of peace and promote a culture of solidarity. Furthermore, we believe that the interaction with young university students who are preparing for diplomatic and international careers can also enrich international organizations through a deeper understanding of young people’s perspectives, enhancing also their creative solutions to crises. The Director-General of the United Nations Agencies in Geneva illustrated in her Message to AESI what the priorities of this health emergency are, but she also encouraged the UN to listen to the new generations. She invited students to send them messages and contributions. The Director-General also expressed her wish to meet with the young AESI members in Geneva when it will be possible. The University will play a great role in the future, not only with respect to the international relations dimension, but above all with the involvement of young people in the process of renewing peace promotion strategies in crisis situations. The United Nations has discovered this great added value and for this we also thank the United Nations Director-General of Geneva.